2021
DOI: 10.1016/j.heliyon.2021.e06868
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline improves the survival of spermatogenic cells via oxidative stress suppression and upregulation of PI3K/AKT pathway in mouse model of testicular torsion-detorsion

Abstract: Testicular torsion-detorsion results in enhanced formation of free radicals which contribute to the pathophysiology of testicular tissue damage. Recent reports have identified protective role of pentoxifylline (PTX) against free radicals. Thus, we determined the protective effect of pentoxifylline against testicular damage in mouse model of testicular torsion-detorsion. Twenty (6 weeks old) male mice were divided into 4 groups of 5 animals each namely: Control (sham operated group), T1 (Torsion-deto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
(72 reference statements)
2
5
0
Order By: Relevance
“…These indicators well showed testicular ischemia-reperfusion injury (Figures 3 and 4 ). They have been widely used in testicular ischemia-reperfusion injury studies [ 86 88 ]. Testicular section stained with Masson trichrome is usually used to quantify collagen accumulation as a marker of fibrosis [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…These indicators well showed testicular ischemia-reperfusion injury (Figures 3 and 4 ). They have been widely used in testicular ischemia-reperfusion injury studies [ 86 88 ]. Testicular section stained with Masson trichrome is usually used to quantify collagen accumulation as a marker of fibrosis [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with Dhulqarnain et al who reported that PTX improved spermatogenic cell survival in mice by activating the Akt signaling pathway. 93…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with Dhulqarnain et al who reported that PTX improved spermatogenic cell survival in mice by activating the Akt signaling pathway. 93 Pentoxifylline treatment led to significant improvements in cardiac structure and function. This was evident by the marked decrease in cardiac hypertrophy and serum levels of CK-MB, LDH and troponin-I.…”
Section: Food and Function Papermentioning
confidence: 99%
“…However, Schramm et al reported that the maximum PTX concentration in seminal plasma was only 75 ng/ml (0.3 μM) ( Schramm and Hinze, 1980 ). Recent two in vitro studies demonstrated the protective impact of PTX on spermatogenesis in mice models with both concentration levels higher than 0.3 μM ( Dhulqarnain et al, 2021 ; Malekzadeh et al, 2021 ). 3) Increased blood perfusion and reduced blood viscosity in testes and epididymis: Pozor and his colleagues confirmed that PTX-treated stallions had significantly higher total arterial blood flow rate than controls, delaying the seasonal decrease of testicular perfusion, without sperm quality and total sperm volume improved ( Pozor et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%